Effect of Zinc Oxide Nanoparticles on the Growth of Malus hupehensis Rehd. Seedlings - Pan, Lianhui; Zhao, Lei; Jiang, Weitao; Wang, Mei; Chen, Xuesen; Shen, Xiang; Yin, Chengmiao; Mao, Zhiquan (Frontiers in Environmental Science, 2022)
Apple replant disease (ARD) is a common disease in apple producing areas, and more and more evidence shows that soil-borne pathogens are the main factor. However, most of the drugs used to kill microorganisms are not friendly to the environment. Therefore, there is an urgent need to identify a method that can effectively eliminate these harmful microorganisms and to construct a microbial community structure that is conducive to plant growth in the soil. Herein, we use four different application technologies: foliar spraying, foliar soaking, root soaking, and soil soaking, to examine the inhibitory effect of zinc oxide nanoparticles (ZnO-NPs) on ARD. This study found that they all promoted the growth of Malus hupehensis Rehd. seedlings, and the plant height was 1.09 times, 1.15 times, 1.26 times, and 1.36 times higher that of the control, respectively. Soil soaking had the best promotion effect, and the changes in the soil microbial community structure after root soaking were analyzed. After treatment with ZnO-NPs, the abundances of Neocosmospora, Gibberella, and Fusarium were reduced, whereas the abundances of Tausonia, Chaetomium, and Mrakia were increased. The copy numbers of Fusarium solani and Fusarium oxysporum were 55.7% and 68.9% lower in the ZnO-NP treatment group than those in the control group, respectively. This study found that after ZnO-NPs were applied to the soil, a new microbial community structure that was conducive to plant growth was formed to overcome ARD. In summary, ZnO-NPs, as a green chemical reagent, can overcome ARD, and it can also be applied to other continuous crops.